The Development of Learning Skill on Microsoft Office Excel in the Content Area of Career and Technology through Demonstrative VDO for Mattayom Suksa Four Students at Kuchanwittayakom School, Secondary Educational Service Area Office 28 - แสงกล้า, สมพงษ์; เอกะกุล, ธีรวุฒิ (Ubon Ratchathani Journal of Research and Evaluation, 2021)
The purpose of this research 1) to develop learning skill on Microsoft Office Excel through demonstrative video, 2) to compare the learning skill before and after using the demonstrative video, and 3) to compare the learning skill of students who learned through demonstrative video versus who learned through regular teaching methods. The subjects were 20 students in the experimental group and 18 students in the control group, selected by means of the purposive random sampling from the population of 42 Mattayom Suksa Four students at Kuchanwittayakom School under the jurisdiction of Secondary Educational Service Area Office 28. The instruments comprised 1) the learning plan that based on demonstrative video and regular teaching method, 2) the learning skill test for action research cycle 1-4, and 3) the record form of after learning.The data were analyzed by means of mean, standard deviation, Wilcoxon range, and Mann Whitney U test. The research findings were as follows: The development of learning skill in this research consisted of four action research cycles such as cycle one : start to use MS Excel, Cycle two : work on cell and cell group, cycle three : categorize the work sheet, and cycle far : decorate the data in worksheet. After students learned through demonstrative video, they had more learning skill than that before using it with the .05 level of statistical significant. The students who learned through the demonstrative video had more learning skill than the students who learned through the regular teaching method with the .05 level of statistical significant.